The Role of Myths in Indigenous Etche Society - Amadi, Emmanuel Echezolochi; Igoniko, Uwom Kenoye Ophagharanan (NIU Journal of Humanities; Vol 11 No 1 (2026): NIU Journal of Humanities, Vol. 11 No. 1, March 2026, 2026)
In traditional Etche society, the curiosity to ascertain the abode of man and his place around his world; his nature of existence, however, form the basis of the role of myths in indigenous Etche society as a road map to the above scenario. The paper posits that myth intimates the people with the idea of the emergence of man into his very abode and the ontological relationship with the supersensible realities. The paper also contends that through myth the peoples’ curiosity about the nature of their existence and interpretation and definition of their place in their environments satisfied their inner thoughts. Data for this study were collected from two major sources (oral interviews; report of the elders and handed down tradition from the repository of custom and traditions of Etche) and secondary sources (published materials). The study also adopts descriptive approach to interpret and analyze the role of myths. Finding reveals that myth has helped the indigenous Etche to interpret the world around them. Keywords: Etche, myth, indigenous Etche society.